If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(9x+9)=9x
We move all terms to the left:
-3(9x+9)-(9x)=0
We add all the numbers together, and all the variables
-9x-3(9x+9)=0
We multiply parentheses
-9x-27x-27=0
We add all the numbers together, and all the variables
-36x-27=0
We move all terms containing x to the left, all other terms to the right
-36x=27
x=27/-36
x=-3/4
| 3=4g− | | x-(-25)=30 | | 4-7n=2+8n | | 7(2x-2)=140 | | 3x+(-30)=-12 | | 7=-4=b | | 5x+2.33=7 | | 7.00+0.75+95.00x=133.50 | | $7.00+$0.75+$95.00x=$133.50 | | 11x-2x+60=11x+34 | | 100r^2+5=69 | | 6x^2-17x-39=0 | | 2.4m−1.2=−0.6m | | 93=4x-(22-x)+25 | | 1/4x+4=8 | | 12-2d/5=6;15 | | 4x(5x+4)=5x+4 | | (x-8)/(2)+(1/3)=7 | | 200m-100m+57,600=61,200-200m | | -4-3x=2x+6 | | ((17-x)/2)/17=0.1 | | 4x2+x+10=0 | | 16k^2-43k+70=0 | | 7c-12=19 | | 2=3g–4 | | x+x+12=2x-12 | | 10=3w+4 | | g4– 3= 2 | | 6.4g+4=3.4g+13 | | 7/x=5/4 | | 7/x=1.25 | | (12t-3t1/2)=0 |